RETRACTED: Genetic Variation in the Androgen Receptor and Measures of Plasma Testosterone Levels Suggest Androgen Dysfunction in Alzheimer’s Disease - Carr, Jessie S.; Bonham, Luke W.; Morgans, Alicia K.; Ryan, Charles J.; Yokoyama, Jennifer S.; Geier, Ethan G.; , Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2018)
Alzheimer’s disease (AD) prevalence varies by sex, suggesting that sex chromosomes, sex hormones and/or their signaling could potentially modulate AD risk and progression. Low testosterone levels are reported in men with AD. Further, variation in the androgen receptor gene (AR) has been associated with AD risk and cognitive impairment. We assessed plasma testosterone levels as a biomarker of AD in male participants from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort. Baseline testosterone levels were significantly different between clinical diagnosis groups (cognitively normal controls, mild cognitive impairment (MCI), or AD), with the lowest testosterone levels in men with AD. Lower baseline testosterone levels were associated with higher baseline clinical severity. Change in testosterone levels between baseline and 1-year follow-up varied by diagnosis; MCI had the greatest decreases in testosterone levels between baseline and 1-year follow-up. Despite differences by clinical diagnosis, there was no association between plasma testosterone and CSF biomarkers of AD pathology. We also tested single nucleotide polymorphisms (SNPs) in AR for association with AD risk in a separate cohort from ADNI and found 26 SNPs associated with risk for AD. The top associated SNP is predicted to be an expression quantitative trait locus for AR in multiple tissues, including brain, with the AD-associated risk allele predicted to confer lower AR expression. Our findings suggest a link between androgen dysregulation and AD through Aβ/tau independent pathways. These effects may be most pronounced during conversion from MCI to dementia.